Paclitaxel and carboplatin plus megestrol acetate in the treatment of advanced non-small cell lung cancer - Thongprasert S. (2014)
The present study evaluated the efficacy and toxicity of paclitaxel and carboplatin with megestrol acetate for patients with stage IIIb and IV non-small cell lung cancer (NSCLC). Forty patients with no prior chemotherapy and Karnofsky performance status of ≥60 were enrolled in the study. There were 18 males and 22 females with a median age of 57.5 years, and the median performance status was 70 per cent. Eleven cases were stage IIIb and 29 cases were stage IV. Twenty-five cases were adenoCA, 12 were squamous cell, 2 were large cell and one was undifferentiated NSCLC. These patients received paclitaxel 135 mg/m2 by intravenous infusion over 24 hours before carboplatin was given at AUC=6 by 2 hours infusion. Megestrol acetate 160 mg/day was given to all patients from day 2 to 14. This treatment produced partial remission in 12 of 39 evaluable patients (30.76%). Toxicity caused mild nausea, vomiting, myalgia, neuropathy, 20.95 per cent grade 3 neutropenia and 4.15 per cent grade 4 neutropenia. Grade 3 thrombocytopenia was 5.4 per cent, without grade 4. There were no statistically significant changes in weight, serum albumin, and quality of life throughout the cycle 1-6. Conclusion: The addition of megestrol acetate to chemotherapy benefitted these patients by minimizing constitute symptoms throughout the treatment period especially in the quality of life, weight loss and stabilized serum albumin.